Dispute Between Waqf Land Vs. Inherited Land (Analysis of the Judge's Presumption as Evidence in Case No. 174/Pdt.G/ 2017/MS.Bna) - Muhammad Husnul; Siti Jum’ah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research discusses the invalidity of the Deed of Replacement of Waqf Pledge Deed on land belonging to the heir who rejected APIAW whose final implication at the appeal stage was that the deed was null and void because contrary to the evidence presented by the plaintiff and the judge's considerations in the form of the judge's guess. The issue of concern is whether the judge's opinion as one of the judge's considerations at the cassation stage can be used as evidence in this case. The research method used is qualitative with a normative juridical approach. The results of the research show that judges can use their assumptions as evidence in their considerations when deciding cases with the assumption that the evidence presented by the plaintiff and defendant has not been able to convince the judge. However, in the end, based on the judge's estimates, it could be concluded that APAIW and the Certificate of Ownership (SHM) had no legal force (not inkracht).